Pelaksanaan Pembelajaran Tahfidz Al-Qur’an Oleh Guru Tunanetra Masa Pandemi COVID-19 di MAN 1 Surakarta - Nurul Maya Astuti; Muhammad Munadi (Institut Agama Islam Negeri Bengkulu, 2021)
ABSTRACTThe purpose of this study was to determine 1) the implementation of learning tahfidz Al-Qur'an by blind teachers during the Covid-19 pandemic in class X IPS 6 MAN 1 Surakarta in the academic year 2019/2020, 2) blind teachers' efforts in creating a conducive atmosphere during the implementation of learning tahfidz Al-Qur'an during the Covid-19 pandemic in class X IPS 6, 3) The reason some class X IPS 6 students are less responsive to blind teachers during the implementation of learning tahfidz Al-Qur'an during the Covid-pandemic 19. This research is a field research (field research) using a qualitative descriptive method. This research was conducted in May-June 2020. The subjects in this study were the Al-Qur'an tahfidz teachers (blind) and students of class X IPS 6. While the informants were the head of the madrasah, the vice principal of the curriculum, the tahfidz coordinator, and the X IPS class guardian. 6. Data collection techniques are carried out by means of observation, interviews, and documentation. In testing the validity of the data, the source and method triangulation techniques were used. Data were analyzed using an interactive analysis model.The results showed that first, the implementation of learning tahfidz Al-Qur'an by blind teachers during the Covid-19 pandemic in class X IPS 6 students was online through the WhatsApp group, using both voice message, text message and call features. Second, the blind teachers' efforts in creating a conducive atmosphere during the implementation of Al-Qur'an tahfidz learning in class X IPS 6 students are blind teachers giving punishment or giving rewards. Third, the reason for some of the actions of students of class X IPS 6 is less responsive to blind teachers in implementing tahfidz Al-Qur'an learning is that blind teachers are less assertive and a lack of parental supervision while lessons are conducted online. Keyword: Learning, Tahfidz Al-Qur'an, Blind Teacher ABSTRAKTujuan penelitian ini adalah untuk mengetahui 1) pelaksanaan pembelajaran tahfidz Al-Qur’an oleh guru tunanetra di masa pandemi covid-19 pada siswa kelas X IPS 6 MAN 1 surakarta tahun pelajaran 2019/2020, 2) usaha guru tunanetra dalam mewujudkan suasana yang kondusif selama pelaksanaan pembelajaran tahfidz Al-Qur’an di masa pandemi covid-19 pada siswa kelas X IPS 6, 3) Alasan beberapa siswa kelas X IPS 6 kurang responsif terhadap guru tunanetra selama pelaksanaan pembelajaran tahfidz Al-Qur’an di masa pandemi covid-19. Penelitian ini merupakan penelitian lapangan (field research) dengan menggunakan metode deskriptif kualitatif. Penelitian ini dilaksanakan pada bulan Mei-Juni 2020. Subjek dalam penelitian ini adalah guru tahfidz Al-Qur’an (tunanetra) dan siswa kelas X IPS 6. Sedangkan informan adalah kepala madrasah, waka bagian kurikulum, koordinator tahfidz, dan wali kelas X IPS 6. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dan dokumentasi. Dalam menguji keabsahan data digunakan teknik triangulasi sumber dan metode. Data dianalisis dengan model analisis interaktif.Hasil penelitian menunjukkan bahwa pertama, pelaksanaan pembelajaran tahfidz Al-Qur’an oleh guru tunanetra di masa pandemi covid-19 pada siswa kelas X IPS 6 adalah secara daring melalui group WhatsApp, baik menggunakan fitur pesan suara, pesan teks, dan panggilan. Kedua, usaha guru tunanetra dalam mewujudkan suasana yang kondusif selama pelaksanaan pembelajaran tahfidz Al-Qur’an pada siswa kelas X IPS 6 adalah guru tunanetra memberikan punishment atau hukuman dan memberikan reward. Ketiga, Alasan beberapa tindakan siswa kelas X IPS 6 kurang responsif terhadap guru tunanetra dalam pelaksanaan pembelajaran tahfidz Al-Qur’an adalah guru tunanetra kurang tegas dan kurangnya pengawasan orangtua selama pembelajaran dilaksanakan secara daring.